Air pollution in moderately polluted urban areas: How does the definition of "neighborhood" impact exposure assessment?. (November 2015) - Tenailleau, Quentin M.; Mauny, Frédéric; Joly, Daniel; François, Stéphane; Bernard, Nadine
Abstract: Environmental health studies commonly quantify subjects' pollution exposure in their neighborhood. How this neighborhood is defined can vary, however, leading to different approaches to quantification whose impacts on exposure levels remain unclear. We explore the relationship between neighborhood definition and exposure assessment. NO2, benzene, PM10 and PM2.5 exposure estimates were computed in the vicinity of 10, 825 buildings using twelve exposure assessment techniques reflecting different definitions of "neighborhood". At the city scale, its definition does not significantly influence exposure estimates. It does impact levels at the building scale, however: at least a quarter of the buildings' exposure estimates for a 400 m buffer differ from the estimated 50 m buffer value (±1.0 μg/m 3 for NO2, PM10 and PM2.5 ; and ±0.05 μg/m 3 for benzene). This variation is significantly related to the definition of neighborhood. It is vitally important for investigators to understand the impact of chosen assessment techniques on exposure estimates. Highlights: Residential building air pollution was calculated using 12 assessment techniques. These techniques refer to common epidemiological definitions of neighborhood. At the city scale, neighborhood definition does not impact exposure estimates. At the building scale, neighborhood definition does impact exposure estimates. The impact of neighborhood definition varies with physical/deprivation variables. Abstract : Ignoring the impact of the neighborhood's definition on exposure estimates could lead to exposure quantification errors that impact resulting health studies, health risk evaluation, and consequently all the decision-making process.